EVIDENCE BASED CASE REPORT (EBCR) : PENGARUH AROMATERAPI LAVENDER TERHADAP PENURUNAN INTENSITAS NYERI PADA PERSALINAN KALA I FASE AKTIF (Politeknik Kesehatan Kemenkes Bandung, 2023)
ABSTRACT Background: WHO reports that there are around 210 million pregnancies worldwide with 20 million cases of labor experiencing pain. Non-pharmacological methods are known to be able to help reduce the risk of pain and illness by paying attention to psychological aspects. Aromatherapy is a non-pharmacological method that works to stimulate the neuroendocrine system to create a calming sensation so that labor pain and pain can be overcome. Purpose: This evidenced base case report is to determine the effect of lavender aromatherapy to reduce pain intensity in the active phase of first stage of labour. Method: The method used is evidenced base case report. Keywords used in the literature search: